Response of phenolic metabolism induced by aluminium toxicity in Fagopyrum esculentum Moench. plants - O. E. Smirnov; A. M. Kosyan; O. I. Kosyk; N. Yu. Taran (The Ukrainian Biochemical Journal, 2015)
Buckwheat genus (Fagopyrum Mill.) is one of the aluminium tolerant taxonomic units of plants. The aim of the study was an evaluation of the aluminium (50 µM) effect on phenolic accumulation in various parts of buckwheat plants (Fagopyrum esculentum Moench.). Detection of increasing of total phenolic content, changes in flavonoid and anthocyanin content and phenylalanine ammonia-lyase activity (PAL) were revealed over a period of 10 days of exposure to aluminium. The most significant effects of aluminium treatment on phenolic compounds accumulation were total phenolic content increasing (by 27.2%) and PAL activity rising by 2.5 times observed in leaves tissues. Received data could be helpful to understand the aluminium tolerance principles and relationships of phenolic compounds to aluminium phytotoxicity.